YOUTH EMPOWERMENT THROUGH ETHICAL AND VALUE EDUCATION FOR SUSTAINABLE NATIONAL DEVELOPMENT (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study focused on youth empowerment through ethical and value education for sustainable national developmentin Ebonyi State. To carry out the study, two specific purposes with two corresponding research questions in line with null hypothesis guided the study. The population of the study was 2,354 graduates registered in Ebonyi State on Youths Economic Empowerment Scheme in Ebonyi State. The sample of the study was 336 graduates which was drawn through Taro Yamane formular while simple random technique was adopted for the study. Structured questionnaire tagged Youth Empowerment through Ethical and Value Education for Sustainable National Development Questionnaire (YEEVESNDQ) was used to elicit responses from the respondents.The structured questionnaire was validated by experts. The reliability of the instrument yielded 0.82 usingCronbach Alpha Procedure.Mean (x) and standard deviation (SD) were used to answer the research questions while t-test was used in testing null hypotheses at 0.05 alpha level of significance. The results of the analysis revealed that ethical and value education should be given to the teenagers irrespective of their areas of specializations, with skills that may enable them engaged in income yielding ventures for self and sustainable development; youth Empowerment involved various processes: participation; welding, fishing, fashion designing. Manipulative skills; furniture making, mining, construction. Intellectual skills. Sculpting; painting, drawing. Comedy, music making among others. Sustainable development is characterized with growth, eradication of poverty, stability in governance, provision of employment and addressing other social concerns. The environment benefits are healthy environment, quality education, rational use of renewable natural resources leading to economic growth and natural development.Based on the finding, the recommendation maintained that government, schools, individuals and organizations should help youths acquire skills and be self-reliance. Besides youths should be put in front of national development for sustainability and building of a strong society